Legal Protection of Street Children for Exploitation in Criminal Law Perspectives - syuhada, esa arung (IJCLS (Indonesian Journal of Criminal Law Studies), 2020)
Article 34 paragraph 1 of the 1945 Constitution states that "the poor and neglected children are maintained by the state. The research method uses normative law, specifications of descriptive analytical research, primary data sources and additional data sources, primary data collection methods and secondary data sources, the method of presenting data is descriptive analytical, data analysis methods of legal material analysis techniques using content analysis.Research results show that the factors that cause the emergence of street children in the Kendal area are economic factors, unemployment, low parent income. The efforts of Kendal District Social Service in handling street children formally and non-formally in Kendal are Preventive Efforts, Repressive Efforts, Rehabilitation Efforts. Legal protection for street children who commit criminal acts committed by street children in the Kendal area, handling is done through open houses. To provide alternatives other than open houses, other forms of opportunity use criminal sanctions as a last resort. street children who do the shopping on the road can be arrested. Then it is accommodated and then given a kind of action (maatregel) with the judge's decision entered into a special penitentiary or rehabilitation institution